2010
DOI: 10.22230/ijepl.2010v5n9a275
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Isolation in Predicting New Principals’ Burnout

Abstract: Professional isolation has hampered the quality of the work experience for employees in and outside public education for decades. This study explores the role that perceived isolation plays in predicting the quality of the work experience among new principals. The analysis tests whether isolation serves as a mediator in the relationship between factors that are known to affect the quality of work life of principals (social support; role stress; and participation in a structured coaching relationship) and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 47 publications
7
57
0
1
Order By: Relevance
“…In the few studies that examined the relationship between social support and burnout in principals, it was found that those who are less isolated are less likely suffer from burnout (Tomic and Tomic 2008;Stephenson and Bauer 2010). Başol (2013) compared levels of burnout among 306 school administrators in Turkey according to their gender and with social support as a covariate.…”
Section: Burnout and Social Supportmentioning
confidence: 99%
“…In the few studies that examined the relationship between social support and burnout in principals, it was found that those who are less isolated are less likely suffer from burnout (Tomic and Tomic 2008;Stephenson and Bauer 2010). Başol (2013) compared levels of burnout among 306 school administrators in Turkey according to their gender and with social support as a covariate.…”
Section: Burnout and Social Supportmentioning
confidence: 99%
“…The absence of interpersonal relationships can also act as a workplace stressor. According to several studies, individuals who experience isolation in the workplace experience greater levels of burnout and dissatisfaction with the workplace (Schlichte, Yssel, and Merbler, 2005;Stephenson and Bauer, 2010). Then again, positive relationships with others in the workplace can provide important elements of support to help insulate and protect individuals from detrimental responses to other stressors in the workplace (Danna and Griffin, 1999).…”
Section: Work and Organizational Characteristicsmentioning
confidence: 99%
“…Miller underestimated the politics surrounding her decisions and the formal hierarchy in her district, which put her in an "awkward position" and professionally isolated her from her colleagues and superiors (Stephenson & Bauer, 2010). She "felt judged for trying to do something right," but realized that she "should have consulted" her superiors before implementing new remedial programs.…”
Section: Whether the Message Was Failure Was Not An Option Or Nobody mentioning
confidence: 99%
“…He received social support from his colleagues and superiors as he implemented complex and substantial changes (Stephenson & Bauer, 2010). Wilson"s ability to negotiate with them for critical resources to push and implement new initiatives as a principal strengthened existing trust and autonomy from central office administrators (Wolcott, 1984 ability to enact educational change, his teachers were exhausted and frustrated during a fastpaced period of initiative implementation and decline.…”
Section: Whether the Message Was Failure Was Not An Option Or Nobody mentioning
confidence: 99%
See 1 more Smart Citation